2014
DOI: 10.12952/journal.elementa.000036
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of surface pCO2 and air-sea CO2 flux in the Amundsen Sea Polynya, Antarctica

Abstract: Partial pressure of CO 2 (pCO 2 ) and dissolved oxygen (DO) in the surface waters of the Amundsen Sea Polynya (ASP) were measured during austral summer 2010-2011 on the Amundsen Sea Polynya International Research Expedition (ASPIRE). Surface pCO 2 in the central polynya was as low as 130 µatm, mainly due to strong net primary production. Comparing saturation states of pCO 2 and DO distinguished dominant factors (biological activity, temperature, upwelling, and ice melt) controlling pCO 2 across regions. Air-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 64 publications
4
44
1
Order By: Relevance
“…The low (more depleted) d 13 C measured in the initial samples is likely due to a phytoplankton response to high aqueous CO 2 concentrations in cold water (Rau et al, 1989) and to the isotopic composition of the respiratory component of the winter CO 2 , which is expected to be depleted. Pre-bloom Winter Water (WW) pCO 2 and DIC values for this region are 455 µatm (Mu et al, 2014) and 2215 µmol C kg −1 (Mu et al, 2014), which would enrich the organic carbon of the phytoplankton, as we observed. In our samples, isotopic ratios increased steadily throughout the first flux event, from initial values of ca.…”
Section: Seasonality and Evolution Of The Annual Flux Eventssupporting
confidence: 69%
“…The low (more depleted) d 13 C measured in the initial samples is likely due to a phytoplankton response to high aqueous CO 2 concentrations in cold water (Rau et al, 1989) and to the isotopic composition of the respiratory component of the winter CO 2 , which is expected to be depleted. Pre-bloom Winter Water (WW) pCO 2 and DIC values for this region are 455 µatm (Mu et al, 2014) and 2215 µmol C kg −1 (Mu et al, 2014), which would enrich the organic carbon of the phytoplankton, as we observed. In our samples, isotopic ratios increased steadily throughout the first flux event, from initial values of ca.…”
Section: Seasonality and Evolution Of The Annual Flux Eventssupporting
confidence: 69%
“…Because these observations were coincident with supersaturated pCO 2 and low dissolved oxygen at the sea surface (Mu et al, 2014), they likely represent upwelled deep waters made buoyant by glacial meltwater. The highest subsurface glacier meltwater concentration was 2.1% and was observed at the DIS outflow (Station 60) at a depth of 82 m, i.e., just before the signal was lost to surface contamination.…”
Section: Assessing Freshwater Sourcesmentioning
confidence: 81%
“…Variability in the import of thick multi-year sea ice from the southern Bellingshausen Sea into the eastern Amundsen Sea, together with variability in the number of icebergs on the outer continental shelf that retain summer sea ice, were other factors contributing to PIP/ASP variability. The sPIP and eASP sea ice changes are important, as they affect the timing, duration and size of these two polynyas and thus impact this biologically productive area (Arrigo and van Dijken, 2003;Arrigo et al, 2012;Alderkamp et al, 2015;Mu et al, 2015), as well as possibly indicating a response to changes in heat and freshwater inputs (Randall-Goodwin et al, 2015;Sherrell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%